(untitled) (Journal Of Educational and Psychological Researches, 2013)
The reality of social and technological change confirms that the classroom environment which prevailing present time is not suitable to emerge a new generation of people that have enough ability to face the contemporary challenges , this fact is as a result of education that is just focus on remembering and knowledge which is based on realities .but the real education should be based on understanding and thinking that is not reflected in our current educational reality . its noticeable that thinking is not take a pivotal role in curriculum this has been confirmed by a study ( al – musswi ,2011 ) ) and may be due all that these curriculum are still interested in quantity without concern in quality so its lost the spirit of renewal and change that meet the requirements of times . Its Worth To Mention That Education In Our Educational Facilities Is Still Captive To The Traditional Methods That Use By Teachers which Represented Indoctrination , Narration And The Positive Role Of Teacher Who Is The Source Of Knowledge And Information . And Learner Is The Negative Recipient . The Ignorance Of A New Strategies And Modern Models And Lack Of Training Courses All These Factors Help Teacher To Use The Traditional Methods That Assist Them To Complete The Syllabus Within Limited Time That Reflected On Students Thinking . So, many reasons oblige our schools to undertake providing appropriate environment to develop the thinking abilities for students in regular and meaningful way that assist them to adapt the requirements of time . where the learning of thinking skills keep valid and renewed for processing information whatever . the classroom and school environment represent the general framework that contains the educational process components, and the extend of harmony and integration between these components directly affected by the general characteristics of classroom and school environment are reflected directly on the general trends for learners , students and parents about the development of thinking processes. We all know the importance of creating a classroom environment, that depend on physical or non physical means, classroom environment has great significance in activating the thinking of learners and support their abilities and potential . and this will only happen in a class environment that offers a set of properties that mentioned previously to stimulate their abilities .so the comfortable psychological environment help student in create his personality ,develop behavior, thinking style and back up his interaction , because this atmosphere fit the process of learning and education, and not separate him ( lentils : 1996 : 37) . Thus facilitating his work and learn without psychological hindrance, as the fearful have produced weak or non-existent. So this research aim to answer these question : 1- What is the meaning of classroom environment and its components ? 2- What is the role of classroom environment in thinking development ? Then The Researcher Suggested To Conduct Studies On The Classroom Environment And Its Relationship With Other Variables Such As Critical Thinking , Intelligence And Academic Achievement And cognitive Thinking